Immobilization of aminoacylase by encapsulation in poly-l-lysine-stabilized calcium alginate beads - Lee, Kong H.; Lee, Pat M.; Siaw, Yew S. (Wiley, 1993)
Aminoacylase I (EC 3.5.1.14) encapsulated in calcium alginate beads stabilized with poly-L-lysine was used for the production of L-phenylalanine by the hydrolysis of a racemic mixture of N-acetyl-DL-phenylalanine. The immobilized aminoacylase was studied with respect to operational stability, thermal stability, effects of pH and temperature and kinetic constants. The leakage of enzyme from the stabilized beads was eliminated. The immobilized enzyme retained high biological activity. The Km and Vmax values for the stabilized beads were 11.11 mmol dm−3 and 0.076 μmol min−1 respectively. The optimum pH and temperature for the hydrolysis were 6.5 and 55°C respectively. Scanning electron micrographs revealed crosslinked structures on the surface of the beads. The operational performances of the beads in a batch reaction and a packed-bed bioreactor for continuous reaction were investigated. With batch reaction, only about 5% of enzyme activity was lost within ten reaction cycles and there was no significant loss of activity over 600 h of continuous operation after equilibrium was reached, and a conversion yield of about 80% was obtained.